Central Line-Associated Bloodstream Infections in Pediatric Intensive Care Unit - Tanıl Kendirli; Ayhan Yaman; Çağlar Ödek; Halil Özdemir; Adem Karbuz; Bilge Aldemir; Haluk Güriz; Can Ateş; Gamze Özsoy; Derya Aysev; Ergin Çiftçi; Erdal İnce (Galenos Yayinevi, 2017)
Introduction: The aim of this study was to determine the frequency of central line-associated bloodstream infections, risk factors, their relationship with catheter insertion location, and the effect of central line-associated bloodstream infections on mortality and pediatric intensive care unit (PICU) length of stay. Methods: This was a prospective, observational and cohort study, carried out between November 2009 and February 2011. During this period, all the patients who had central-line were monitored for central line-associated bloodstream infection. Results: In the study period, 275 patients were admitted to our PICU. The frequency of invasive device usage was 38.9% (107) for central venous catheter, 38.2% (105) for mechanical ventilation, 53.3% (147) for urinary catheter, and 11.3% (32) for artery line. Central line-associated bloodstream infection was detected in 16 (14.8%) of the patients and 23 central line-associated bloodstream infection attacks were observed. There were 14 central line-associated bloodstream infection attacks in 1.000 central venous catheter usage days. There were 168 patients without central venous catheter and 4 (2.4%) of them had blood stream infection. Thirty-six patients died and the mortality rate was 13%. Five of these patients (13.8%) died due to central line-associated bloodstream infection, 27 (25%) of them had central venous catheter and 9 (6%) of them did not (p=0.001). Conclusion: In conclusion, central line-associated bloodstream infection is one of the serious healthcare-associated infections, and it is an important cause of morbidity and mortality in PICUs.